PENGARUH PEMBERIAN DOSIS PUPUK KANDANG KOTORAN AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KUBIS BUNGA PADA TANAH GAMBUT - man, budi; jani, nur; hadijah, siti (Jurnal Sains Pertanian Equator, 2014)
Utilization of peat soil for cauli flower plant constrained in some limiting factors, such as the physical, chemical and biological unfavorable. One attempt to solve the problem on peat soil is application of chicken drop. This study aimed to determine the effect and the best dose of chicken drop on the growth and yield of cauli flower plant on peat soil. This research was conducted in a plastic house located in Kalimas Village, Sub district in Sungai Kakap, Kubu Raya district on May 23rd until August 16th, 2013. The research method used the completely randomized to design ( CRD ), it consists of six treatment levels, four replications and each treatment levels consist of three plant samples. Treatment levels were p1 = 360 g / polybag , p2 = 540 g / polybag , p3 = 720 g / polybag , p4 = 900 g / polybag , p5 = 1080 g / polybag , p6 = 1260 g / polybag . Observation variable were the number of leaves, leaf area , fresh weight of mass crop, crop diameter and root volume . The results show that aplication of chicken drop on peat soil gives the same response in all variables except leaf area at week 8th. Dose 540 g/ polybag gives the best results compare wits the other treatments. Keywords: Cauliflower, Chicken Drop, Peat Soil